The association of cyberbullying with major depressive disorders among Bangladeshi female adolescents: findings from the Bangladesh adolescent health and wellbeing survey 2019-20 - Syed Toukir Ahmed Noor; Md. Fakrul Islam; Md Sabbir Hossain; Raisha Binte Islam; Rajon Banik; Shafayatul Islam Shiblee; Sarker Mohammad Nasrullah; Sahar Raza (BMC Psychiatry)
Abstract Background Cyberbullying refers to the act of using digital technology to engage in bullying. It involves the intentional use of the internet to demean or denigrate individuals, and it has been linked to substantial psychological distress globally. Despite its increasing prevalence, there remains a gap in nationwide research on its association with the mental well-being of female adolescents in Bangladesh. Objective The main objective of this study was to understand the association of cyberbullying with major depressive disorder (MDD) among female adolescents in Bangladesh. Methods We used secondary data from the 2019–20 Bangladesh Adolescent Health and Wellbeing Survey (BAHWS), a nationally representative survey. A multiple logistic regression model was used to identify the possible association between cyberbullying and MDD. Findings Among the 4,984 female adolescents surveyed, 8% (95% CI: 7–9) reported experiencing cyberbullying within the past 12 months, and 12% (95% CI: 11–14) were found to have MDD. Among those who had experienced cyberbullying, the prevalence of MDD was 31%. Additionally, a dose‒response relationship was observed, where the burden of MDD increases with the frequency of cyberbullying experiences. Compared with those who did not experience cyberbullying, adolescents who faced any form of cyberbullying in the past 12 months were almost four times more likely (AOR: 3.97, 95% CI: 3.12–5.05) to have MDD. Conclusion Cyberbullying is a significant issue among female adolescents in Bangladesh, with a higher risk of MDD linked to increased exposure. Accessible reporting mechanisms and timely counselling through teachers or healthcare providers can help reduce the long-term mental health impact of cyberbullying. Clinical trial number Not applicable.